(untitled) (Journal of Geography and Environmental Management, 2016)
In massage settle an arguments of author at regime of microelements (F) and some heave metals (Cu, Zn, Mn, Pb, Cd etc.) in water of rivers of Northern slope Ile Alatau for 2009–2010 years.